Antifungal Effect of Ascaris suum, Goeze Pseudocoelom and Perienteric Body Fluid to Candida albicans, (C.P. Robin) Berkhout In Vitro - Jayadisastra, Zakka Zayd Zhullatullah; Sari, Yulia; Haryati, Sri (Nexus Biomedika, 2016)
Introduction: Ascaris suum, Goeze pseudocoelom and perienteric body fluid is suggested to have antifungal effect to Candida albicans, (C.P. Robin) Berkhout because of Ascaris suum antibacterial factor (ASABF) which presents in pseudocoelom body fluid and neuropeptide-like protein 29 and caenacin-2 which present in perienteric body fluid. This research is conducted to prove the antifungal effect of Ascaris suum, Goeze pseudocoelom and perienteric body fluid to Candida albicans, (C.P. Robin) Berkhout in vitro. Methods: This was a quasi-experimental research. Candida albicans, (C.P. Robin) Berkhout speciments were tested using Ascaris suum, Goeze pseudocoelom and perienteric body fluid with concentration of each were 80%, 90%, and 100%. Specimens were incubated in temperature of 37oC for 24 hours and the inhibitory zone was measured. Result: Ascaris suum, Goeze pseudocoelom and perienteric body fluid didnât create any inhibitory zone in Candida albicans, (C.P. Robin) Berkhout inoculation. Conclusion: Ascaris suum, Goeze pseudocoelom and perienteric body fluid didnt have antifungal effect to Candida albicans, (C.P. Robin) Berkhout. Keywords: Candida albicans, Ascaris suum, Pseudocoelom Body Fluid, Perienteric Body Fluid.Â